A história de vida de crianças e adolescentes como mediadora da reintegração no contexto familiar - Bento, Rilma (2010)
This paper presents an study ex-post factum concerning the research-action-in-the-action of the development of a methodology applicable in the process of reintegrating in the familiar context the children and teenagers attended by institutions. The research was based upon the principle that the life history of institutionalized children could be helpful in their process of familiar reintegration. The investigation was based in cases of children and teenagers of different ages, object of psychologic monitoring during the years 2006 and 2007, sent by the judiciary of childhood and youth of São Caetano do Sul, in the metropolitan region of São Paulo. Based upon a qualitative approach, the study was performed in two cases, emphasizing the methodology utilized in the monitoring above mentioned. Depositions were collected from the personal that participated in the process and the professionals that attended in the elaboration of the methodology. The theoretical base of the study utilized concepts of affective privation, formation and breaking of affective relations, institutional foster care, and social nets as fundamental aspects, not only for understanding the cases studied, but all the process developed for reintegrate the children in the familiar context. The results obtained showed the importance of establishing a proposal for the intervention aiming the reconstruction of the history of life of the children and teenagers as helpful mediators in the process of reintegration in the family, assuring them respect in their singularity